Islamic influence on Christian legislation in the kingdom of Castile. Issue 3 (27th May 2019) - Echevarria, Ana
ABSTRACT: This article explores the interaction of legal systems in the context of the mixed religious society of the Iberian Peninsula, and the impact of minority law and its practitioners on social order. The kingdom of Castile is studied in the longue durée, involving more than four centuries of co-existence of Muslims, Jews and Christians, in order to assess the influence of a Muslim population and its law on the transformations taking place in the Christian legal system of the kingdom. This period shows great changes in the development of both Christian royal law and Islamic legal tradition that made a dialogue between them possible, and which produced new forms of codification that responded to the challenges of mixed societies. The influence of Islamic laws and institutions on Castilian royal law is unparalleled in medieval Europe, except Norman Sicily and the Crusader States.